PENGARUH METODE PQ4R DISERTAI QUESTION STUDENT HAVE PADA MATERI STRUKTUR TUMBUHAN KELAS VIII SMP - Marika, Ade; Hardigaluh, Basuki; Ariyanti, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the use of learning method PQ4R accompanied Question Student Have towards students learning outcome in matter of plant structure in grade VIIIth SMP Negeri 2 Pontianak. The method of this research was quasi experimental design with nonequivalent control group design. The study samples consists of two classes namely grade VIII A as experiment class and grade VIII B as control class. The sampling technique was intact group. Instruments used in this research 20 items of multiple choice test. The average student learning outcomes experiment class was 77,50 and control class was 73,55. From U Mann-Whitney test obtained Zcount (-1,29) > Ztable (-1,96), the mean that there were difference between students learning outcome which taught used the method of PQ4R accompanied Question Student Have and taught used the conventional method. Whereas from Effect Size, the method of PQ4R accompanied Question Student Have in matter of plant structure extend contibute 10,64% towards students learning outcome. This indicated learning method PQ4R accompanied Question Student Have influence on students learning outcome in matter of plant structure. Keywords:Learning Method PQ4R, Question Student Have, Learning Outcome, Plant Structure